Immunogenicity and protective efficacy of seven candidate vaccines boosted with recombinant proteins, whole-cell bacterins of three serotypes of Mannheimia haemolytica, and an emulsion-type adjuvant - Balevi, Aslı; Toslak, Emine Eda; Uslu, Ali; Sayın, Zafer; Erganis, Osman (Frontiers in Veterinary Science, 2025)
IntroductionMannheimia haemolytica is a primary cause of bovine respiratory disease, leading to substantial economic losses in the livestock industry. Current commercial vaccines offer limited cross-serotype protection, and the rising prevalence of serotype 6 (S6) necessitates the development of more effective vaccines. This study aimed to develop novel candidate vaccines, including monovalent, bivalent, trivalent, and recombinant protein-based on S1, S2, and S6 serotypes of M. haemolytica formulations, to create an in-house ELISA with eight coating antigens.MethodsFive hundred lung samples from calves and sheep with respiratory infection symptoms were analyzed. Three M. haemolytica master seed strains (S1, S2, and S6) with diverse phenotypic and genotypic characteristics were selected. Recombinant leukotoxin (lkt) and S1-specific antigen (SSA-1) proteins were produced and used in the development of both vaccines and in-house ELISA. The eight coating antigens utilized were derived from whole-cell pellets, supernatant proteins of S1, S2, and S6, and recombinant lkt and SSA-1. Seven candidate vaccines (three monovalent, one bivalent, one trivalent, and two recombinant) were formulated with Montanide™ ISA 206 VG or Freund’s complete adjuvant. Female Swiss albino mice (n = 18 per group) were vaccinated twice at 21-day intervals via the intramuscular route.ResultsS6 strains had the highest prevalence, with 43.07%. Interestingly, S6 strains expressed a prominent band at approximately 250 kDa, potentially causing haemorrhagic effects in mice. The S2 pellet performed best as an ELISA-coating antigen. The trivalent vaccine with Montanide™ ISA 206 VG provided the best protection in mice. Seropotency vaccine efficacy and challenge vaccine efficacy of trivalent vaccine were 95.8 and 100%, respectively. According to multinomial logistic regression analysis, the greatest odds ratio (0.97) was obtained from the trivalent vaccine.ConclusionThe haemorrhagic effects observed with S6 highlight the importance of including this serotype in future vaccines. The trivalent S6 vaccine with Montanide™ ISA 206 shows promise for improved protection against diverse M. haemolytica strains. Further research, including challenge studies in target animals, is needed to confirm these findings and evaluate field efficacy.